PENGARUH SLOW DEEP BREATHING DAN AROMATERAPI LAVENDER TERHADAP KUALITAS TIDUR PADA LANSIA - Siti Zahroul Laili; Linda Ishariani; Melani Kartikasari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
The elderly may experience sleep disturbances which result in poor sleep quality. One of the ways to deal with poor sleep quality is slow deep breathing and lavender aromatherapy. This study aims to analyze the effect of slow deep breathing and lavender aromatherapy on sleep quality in the elderly. The design of this study was a pre-experimental design with a one-group pretest-posttest design approach. The population of all elderly aged 60-74 years was 60 people, a sample of 18 respondents was taken using purposive sampling technique. The independent variables in this study are slow deep breathing and lavender aromatherapy and the dependent variable is sleep quality. Data collection in this study used a sleep quality questionnaire, namely the PSQI (Pittsburgh Sleep Quality Index). This study used the Wilcoxon test with a P-Value significance of 0.000 <α 0.05. The results of this study showed that the quality of sleep before being given slow deep breathing and lavender aromatherapy interventions were all (100%) in the bad category. After being given the intervention of slow deep breathing and lavender aromatherapy, almost all sleep quality (77.8%) was in the good category. There is an effect of slow deep breathing and lavender aromatherapy on sleep quality in the elderly with a P-Value of 0.000 <α0.05. The combination of slow deep breathing and lavender aromatherapy every day 20 minutes before going to bed at night can regulate the onset of sleep and provide a relaxing and sedative effect. The elderly are advised to apply slow deep breathing and lavender aromatherapy independently to improve sleep quality as an alternative if they experience sleep disturbances.